Histologic heterogeneity and syndromic associations of non-ampullary duodenal polyps and superficial mucosal lesions. Issue 12 (December 2021) - Carbone, Riccardo; Rovedatti, Laura; Lenti, Marco Vincenzo; Furlan, Daniela; Errichiello, Edoardo; Gana, Simone; Luinetti, Ombretta; Arpa, Giovanni; Alvisi, Costanza; De Grazia, Federico; Valente, Enza Maria; Sessa, Fausto; et al.
Abstract: Background: Duodenal polyps and superficial mucosal lesions (DP/SMLs) are poorly characterised. Aims: To describe a series of endoscopically-diagnosed extra-ampullary DPs/SMLs. Methods: This is a retrospective study conducted in a tertiary referral Endoscopy Unit, including patients who had DPs or SMLs that were biopsied or removed in 2010–2019. Age, gender, history of familial polyposis syndromes, DP/SML characteristics were recorded. Histopathological, immunohistochemical and molecular analyses were performed. Results: 399 non-ampullary DP/SMLs from 345 patients (60.6% males; median age 67 years) were identified. Gastric foveolar metaplasia represented the most frequent histotype (193 cases, 48.4%), followed by duodenal adenomas (DAs; 77 cases, 19.3%). Most DAs (median size 6 mm) were sessile (Paris Is; 48%), intestinal-type (96.1%) with low-grade dysplasia (93.5%). Among syndromic DAs (23%), 15 lesions occurred in familial adenomatous polyposis 1, two were in MUTYH -associated polyposis and one was in Peutz-Jeghers syndrome (foveolar-type, p53-positive, low-grade dysplasia). Only one (3.3%) tubular, low-grade DA showed mismatch repair deficiency (combined loss of MLH1 and PMS2, heterogeneous MSH6 expression), and it was associated with a MLH1 gene germline mutation (Lynch syndrome). Conclusion: DPs/SMLs are heterogeneous lesions, most of which showing foveolar metaplasia, followed by low-grade, intestinal-type, non-syndromic DAs. MMR-d testing may identify cases associated with Lynch syndrome.